MEDIA IKLAN BANNER SEBAGAI MEDIA KAMPANYE PEMILU LEGISLATIF 2014 - Anita Trisiah (Wardah, 2013)
There are many ways people use to campaignate themselves to attract others’ attention so that the voters will give them the vote. One of the ways used is through the advertisement.  Advertisement is a way to create choice and awareness. Principally, advertisement is a form of message presentation conducted by communicator nonpersonally through media to communicate. As we know,there will be12 parties participate in 2014 election. Each of the parties has their candidates in local and national level. And each of the candidates try their best to promote themselves through advertisement, and commonly through banner that people will know them and finally give their their voice. Through the literature and observation, the writer found out that banner mostly used by the legislative candidates to gain the voices for the election. it modified in its maximum level to attract people attention